IMF Staff Papers, Volume 56, No. 1. (IMF Staff Papers; IMF Staff Papers, 2009)
This special issue brings together world-renowned experts to provide a systematic and critical analysis of the costs and benefits of financial globalization. Contributors include Kenneth Rogoff, Maurice Obstfeld, Dani Rodrik, and Frederic S. Mishkin.